Origin of the dolomite in the Buqu Formation (Mid-Jurassic) in the south depression of the Qiangtang Basin, Tibet: Evidence from petrographic and geochemical constraints - Wan, Youli; Lin, Jiashan; Zhao, Zhan; Wang, Zhonglin (Frontiers in Earth Science, 2022)
Abstract:The Qiangtang basin is a new field of hydrocarbon exploration,in which the Buqu Formation dolomite reservoirs have attracted increasing attention in recent years.To determine the origin of these dolomites, petrographic study, fluid inclusion thermometry dating,and C-O and Sr isotopic dating were performed.The results have revealed the genesis and evolution of different types of dolomite matrix and cements, summarized as follows:(1)The dolomite texture in the study area is closely related to its formation environment and process and can be divided into the primary fabric well-preserved dolomite(Rd1),primary fabric poorly-preserved dolomite,and dolomite filling.The primary fabric-poorly-preserved dolomite includes fine-grained euhedral dolomite(Rd2),fine-grained planar subhedral dolomite(Rd3)and medium- to coarse-grained anhedral dolomite (Rd4). The dolomite filling includes fine-grained planar subhedral cave-filling dolomite (Cd1) and medium-to coarse-grained anhedral, saddle dolomite (Cd2).(2)Rd1 has δ13C‰PDB of 3.42‰-4.23‰, δ18O‰PDB from -4.22‰ to-3.37‰,and 87Sr/86Sr of 0.707654-0.708176,and it was formed in the contemporaneous or penecontemporaneous stage at low temperatures by mimic replacement related to seawater evaporation. Abundant supersaturated dolomitization fluids made it favorable to the preservation of its primary dolomite texture. (3) Rd2 has δ13C‰PDB of 3.18‰-4.11‰, δ18O‰PDB from -4.56‰ to -4.23‰, and 87Sr/86Sr (0.707525-0.708037), while Rd3 has δ13C‰PDB of 2.72‰-4.42‰, δ18O‰PDB from -6.57‰ to-5.56‰,and 87Sr/86Sr of 0.707432-0.707990.They were both formed at low temperatures in the shallow-burial stage, when the dolomitization fluid was mainly derived from seawater.Excessive dolomitization during the late shallow-burial stage caused destruction of dolomite crystals from euhedral to subhedral.(4)Rd4 has δ13C‰PDB of 3.24‰-4.14‰,δ18O‰PDB from-8.22‰ to-6.37‰, and 87Sr/86Sr of 0.707234-0.707884,and it resulted from dolomitization or recrystallization at high temperatures in the medium- to deep-burial stage. The crystal curvature was caused by high environment temperatures.(5)Cd1 has δ13C‰PDB of 3.02‰ , δ18O‰PDB of-5.13‰,and 87Sr/86Sr of 0.708147 and was formed as the cavern filling before the shallow-burial stage.Cd2 has δ13C‰PDB of-0.09‰-3.38‰,δ18O‰PDB from-10.41‰ to 8.56‰,and 87Sr/86Sr of 0.708180-0.708876,and it was related to the collisional orogeny between the Lhasa termite and the Qiangtang Basin in the late Early Cretaceous.Fluids in the overlying and underlying clastic strata of the Buqu Formation were driven by the thermal hot spot in a compressional tectonic setting.Meanwhile,these fluids caused negative shifts of the oxygen isotope compositions of the earlier dolomite.